Differential carotenoid composition of the B875 and B800-850 photosynthetic antenna complexes in Rhodobacter sphaeroides 2.4.1: involvement of spheroidene and spheroidenone in adaptation to changes in light intensity and oxygen availability. - Yeliseev, A A (1996)
Rhodobacter sphaeroides 2.4.1 is a member of the nonsulfur purple facultative photosynthetic proteobacteria, capable of growth under a variety of cultivation conditions. In addition to the structural polypeptides and bacteriochlorophyll, the two major antenna complexes, B875 and B800-850, contain a variety of carotenoids which are an important structural and functional component of the membrane-bound photosynthetic complexes of this bacterium. Two major carotenoids, spheroidene and its keto derivative, spheroidenone, are differentially synthesized by R. sphaeroides, depending on the growth conditions. Spheroidene prevails during growth under anaerobic conditions and low light intensities, whereas spheroidenone is predominant in semiaerobically grown cells or during anaerobic growth at high light intensities. In this study, we demonstrate that in wild-type cells, spheroidene is predominantly associated with the B800-850 photosynthetic antenna complex and spheroidenone is more abundant in the B875 complex. Exploiting mutants defective in the biosynthesis of either the B875 or B800-850 light-harvesting complex, we demonstrate an association between the formation of either the B875 or B800-850 complex, on the one hand, and the accumulation of spheroidenone or spheroidene, on the other. The possible involvement of the conversion of spheroidene to spheroidenone as a significant control mechanism involved in the adaptation of R. sphaeroides to changes in light intensity and oxygen tension is discussed.